Healthcare practitioners' experiences of breaking bad news: A critical interpretative meta synthesis. (February 2023) - Francis, Laura; Robertson, Noelle
Abstract: Objective: To provide an overview of healthcare practitioners' experiences of breaking bad news. Method: Interpretative meta synthesis of 14 qualitative papers identified through a systematic search. Data were extracted and constructs elicited via reciprocal translational analysis. Results: Findings comprised four inter-connected themes: (1) Discomfort, particularly difficult emotional and physical responses to breaking bad news; (2) Relational distress, connected to attachment and identification with patients; (3) Inadequate clinician, indicating the fear and rumination about the possibility of getting it wrong and the subsequent self-blame; and (4) Only human, highlighting a culture of invulnerability where practitioner self-care is deprioritised. Conclusions: Breaking bad news provokes significant distress for practitioners, particularly where they experience strong attachment to or identification with a patient. Breaking bad news was understood as an isolating experience and staff's non-disclosure of difficulties appeared to sustain a culture of invulnerability in which admission of distress was not encouraged. Practice implications: Given the adverse impacts and potential for practitioner burnout, organisations should acknowledge ramifications and offer time for staff to process the delivery of bad news, promote a culture of collective care and provide space for reflective practice. Highlights: Breaking bad news provokes significant distress for practitioners. Breaking bad news is understood as an isolating experience. Non-disclosure of difficulties appeared to sustain a culture of invulnerability. Organisations should offer time for staff to process the delivery of bad news. A culture of collective care and space for reflective practice are recommended.